Short-Term Variability of Hα Emission Line Parameters in π Aqr as a Be Star - Taufieq Zannata Ramadhan; Aprilia (Spektra: Jurnal Fisika dan Aplikasinya, 2025)
B-emission (Be) star is a B type star which shows emission line in its spectrum, especially Hα, caused by the disk surrounding it. One of the Be stars, π Aqr, is a binary Be star in constellation Aquarius which shows variability of double-peaked Hα emission line caused by a circumstellar disk around the primary component. We aim to study recent physical phenomenon which occurs in the disk of π Aqr star based on its spectral data from 2004 to 2024, retrieved from BeSS database, by analyzing the variability of its Hα emission line parameters: the Violet-to-Red peak ratio (V/R), Emission-to-Continuum ratio (E/C), Equivalent Width (EW), Full Width at Half Maximum (FWHM), and peak separation. The variation of V/R ratio from 2004 to 2019 shows period of 84.1 days which corresponds with orbital period of the binary system. However, in 2024, the V/R variability does not show similar cycle period in previous years as the red peak strength dominates throughout most of the year. The EW and E/C increase, indicating rising disk activity and expansion until 2024. Overall increase of red and blue peak separation roughly suggests expansion in Hα region in the disk.